CMOS analog circuit design - Allen, Phillip E. (Oxford University Press, 2002)
After years of anticipation, respected authors Phil Allen and Doug Holberg bring you the second edition of their popular textbook, CMOS Analog Circuit Design. From the forefront of CMOS technology, Phil and Doug have combined their expertise as engineers and academics to present a cutting-edge and effective overview of the principles and techniques for designing circuits. Their two main goals are